2019
DOI: 10.1002/htj.21420
|View full text |Cite
|
Sign up to set email alerts
|

Laminar natural convection of power‐law fluids over a horizontal heated flat plate

Abstract: Natural convection of power-law fluids over a horizontal flat plate with constant heat flux is studied. The stretching transformations relating the similarity forms of the boundary layer velocity, pressure, and temperature profiles are applied to the governing boundary layer equations. The resultant set of coupled ordinary differential equations are solved analytically and numerically using the integral method and the finite difference method, respectively. The results are presented for the details of the velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The influence of velocity slip on the MHD peristaltic transport of a Casson fluid and transfer of heat through an asymmetric channel cantaining a porous media was assessed 35 . Over a horizontal, flat plate with a constant heat flux, natural convection of power-law fluids was investigated 36 . Many authors have recently investigated the MHD convection for diffrent fluids under effect of heat transfer in the articles [37][38][39] and 40,41 .…”
Section: List Of Symbols Amentioning
confidence: 99%
“…The influence of velocity slip on the MHD peristaltic transport of a Casson fluid and transfer of heat through an asymmetric channel cantaining a porous media was assessed 35 . Over a horizontal, flat plate with a constant heat flux, natural convection of power-law fluids was investigated 36 . Many authors have recently investigated the MHD convection for diffrent fluids under effect of heat transfer in the articles [37][38][39] and 40,41 .…”
Section: List Of Symbols Amentioning
confidence: 99%
“…The group theory analysis [29] provides that the following combinations of the variables give the absolute invariants:…”
Section: Mathematical Analysismentioning
confidence: 99%
“…The study revealed that increase in nanoparticles volume fraction affect the entropy production more than enhancement in heat transfer rate. A Bahmani [31] investigated horizontal flat plate HXs under natural convection and constant heat flux. The results revealed that for Prandtl number higher than 1, low Nusselt number was achieved.…”
Section: Introductionmentioning
confidence: 99%